The Role of Interfaces and Charge for Chemical Reactivity in Microdroplets - LaCour, R. Allen; Heindel, Joseph P.; Zhao, Ruoqi; Head-Gordon, Teresa (Journal of the American Chemical Society, 2025)
A wide variety of reactions are reported to be dramatically accelerated in aqueous microdroplets, making them a promising platform for environmentally clean chemical synthesis. However, to fully utilize the microdroplets for accelerating chemical reactions requires a fundamental understanding of how microdroplet chemistry differs from that of a homogeneous phase. Here we provide our perspective on recent progress to this end, both experimentally and theoretically. We begin by reviewing the many ways in which microdroplets can be prepared, creating water/hydrophobic interfaces that have been frequently implicated in microdroplet reactivity due to preferential surface adsorption of solutes, persistent electric fields, and their acidity or basicity. These features of the interface interplay with specific mechanisms proposed for microdroplet reactivity, including partial solvation, possible gas phase channels, and the presence of highly reactive intermediates. We especially highlight the role of droplet charge and associated electric fields, which appears to be key to understanding how certain reactions, like the formation of hydrogen peroxide and reduced transition metal complexes, are thermodynamically possible in microdroplets. Lastly, we emphasize opportunities for theoretical advances and suggest experiments that would greatly enhance our understanding of this fascinating subject.